Biological and morphological parameters of Dysdercus maurus fed with low- or high-oil cotton seeds - Silva, Carlos Alberto Domingues da; Galdino, Josivaldo da Silva; Carvalho, Thiele da Silva; Zanuncio, José Cola (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to determine the biological and morphological parameters of Dysdercus maurus fed with cotton (Gossypium hirsutum) seeds with a high or low oil content, as well as to identify genotypes to be used in breeding programs as sources of resistance to this stink bug. The development, survival, and reproduction of the cotton stainer bug were determined in a completely randomized experimental design. The treatments consisted of the insect nymphs being feed with cotton seeds of the CNPA 2001-5581 (high oil content) or CNPA 2001-5087 (low content) genetic line. Survival, weight, and morphological parameters of the bug were determined. The survival of second- and third-instar nymphs and of the total nymph stage of D. maurus was lower with cotton seeds with a low oil content. The body length and head width of D. maurus adults were greater, but pronotum length and width were smaller and the females heavier with cotton seeds with a high oil content. Low-oil cotton genotypes can reduce populations of the stainer bug.